2000
DOI: 10.1007/s002460010038
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiography and 24-Hour Electrocardiographic Ambulatory Recording (Holter Monitor) Studies in Children Infected with Human Immunodeficiency Virus Type 1

Abstract: Limited data are available on the electrocardiogram and ambulatory electrocardiogram recording (Holter) in children infected with the human immunodeficiency virus type 1 (HIV-1). The purpose of this study was to estimate the prevalence and cumulative incidence of rhythm and conduction abnormalities in HIV-1-infected children. Electrocardiograms and Holter monitoring studies were performed annually on 205 HIV-1-infected children enrolled after 28 days of life (group I), 93 HIV-1-infected infants enrolled during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 12 publications
0
36
0
Order By: Relevance
“…Despite the known benefits of ATV, there are concerns about its potential adverse effects of inducing cardiac arrhythmia [2,3] . Similar to other PIs [4][5][6][7] , ATV has previously been reported to be specifically associated with acquired long-QT syndrome, druginduced QT prolongation, and torsades de pointes (TdP) in HIV-infected patients [8][9][10] . However, these results contradict other recently published studies [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the known benefits of ATV, there are concerns about its potential adverse effects of inducing cardiac arrhythmia [2,3] . Similar to other PIs [4][5][6][7] , ATV has previously been reported to be specifically associated with acquired long-QT syndrome, druginduced QT prolongation, and torsades de pointes (TdP) in HIV-infected patients [8][9][10] . However, these results contradict other recently published studies [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…
Southwestern Medical Center at Dallas,and 6 Veterans Affairs North Texas Health Care System, Dallas, TX, USA Background Atazanavir (ATV), an HIV protease inhibitor (PI) that may be preferred for the treatment of HIV-infected patients with cardiovascular comorbidities because of its favourable effects on plasma lipids, has been associated with cardiac rhythm disturbances.
ObjectiveTo quantify the effect of ATV on corrected QT (QTc) and QTc dispersion (QTd), markers of the potential for cardiac dysrhythmia, in patients switching from other PIs to ATV.
MethodsIn this prospective, single-centre, open-label study, 12-lead electrocardiograms were performed for subjects at baseline, 2 h after the first dose of ATV, and 1 month after initiation of ATV.
ResultsTwenty-one patients (19 received ritonavir-boosted ATV) completed the study. There was a trend towards an increase in the QTc at 2 h after the first dose [mean AE standard deviation 3.19 AE 8.0 ms; 95% confidence interval (CI) À 0.47 to 6.85 ms; P 5 0.084].
…”
mentioning
confidence: 99%
“…Southwestern Medical Center at Dallas,and 6 Veterans Affairs North Texas Health Care System, Dallas, TX, USA Background Atazanavir (ATV), an HIV protease inhibitor (PI) that may be preferred for the treatment of HIV-infected patients with cardiovascular comorbidities because of its favourable effects on plasma lipids, has been associated with cardiac rhythm disturbances.…”
mentioning
confidence: 99%
“…These findings indicate that repolarization adaptation to heart rate was preserved. Saidi et al (34) studied the Bazett-corrected QT interval on resting surface ECG in perinatally HIV-infected children from birth to 10 years of age, and observed that average QTc interval showed a significant variation throughout the first decade of life. In the present study, all MQTc intervals were consistently comparable to those reported by Saidi et al (34) for an equivalent age group.…”
Section: Discussionmentioning
confidence: 99%
“…Saidi et al (34) studied the Bazett-corrected QT interval on resting surface ECG in perinatally HIV-infected children from birth to 10 years of age, and observed that average QTc interval showed a significant variation throughout the first decade of life. In the present study, all MQTc intervals were consistently comparable to those reported by Saidi et al (34) for an equivalent age group. On the other hand, a physiological nighttime prolongation in QTc interval has been observed in healthy adults (35) and healthy children (36), a consequence of increased parasympathetic drive during this period.…”
Section: Discussionmentioning
confidence: 99%